2022
DOI: 10.3389/fphy.2022.866656
|View full text |Cite
|
Sign up to set email alerts
|

A High-Efficiency and Reconfigurable Rectenna Array for Dynamic Output DC Power Control

Abstract: In this paper, an output power reconfigurable rectenna array is proposed for the first time to harvest RF energy. The proposed rectenna array can be used to capture abundant RF energy with high conversion efficiency in a wide range of input power levels and load impedance at 1.88, 2.35, 3.5, and 4.9 GHz simultaneously. The output DC power of the proposed rectenna array can be changed exponentially by altering the on-off state of the switches located between the antenna and the rectifier. The measured result sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The EM characteristics of metamaterials rely on the pattern and order of the meta-atom (Cui, 2017). In the past few decades, metamaterial-inspired devices, such as the frequency selective filter (Khan and Eibert, 2018;Zhang et al, 2021a), perfect absorber (Peng et al, 2019;Zhang et al, 2021b), holographic imaging (Tsai et al, 2013;Wan et al, 2017), and meta-lens (Pendry, 2000), have found variety of applications in academia and industries (Zhang et al, 2021c;Dong et al, 2022;Wang et al, 2022). Among these applications, metamaterial absorbers (MMA) have been realized in the spectrum ranging from microwave to optics.…”
Section: Introductionmentioning
confidence: 99%
“…The EM characteristics of metamaterials rely on the pattern and order of the meta-atom (Cui, 2017). In the past few decades, metamaterial-inspired devices, such as the frequency selective filter (Khan and Eibert, 2018;Zhang et al, 2021a), perfect absorber (Peng et al, 2019;Zhang et al, 2021b), holographic imaging (Tsai et al, 2013;Wan et al, 2017), and meta-lens (Pendry, 2000), have found variety of applications in academia and industries (Zhang et al, 2021c;Dong et al, 2022;Wang et al, 2022). Among these applications, metamaterial absorbers (MMA) have been realized in the spectrum ranging from microwave to optics.…”
Section: Introductionmentioning
confidence: 99%